Localization performance of cochlear implant users with a real-time bilaterally-synchronized sound coding strategy that provides explicit interaural timing cues with mixed rates of stimulation - Borjigin, Agudemu; Dennison, Stephen R.; Kan, Alan; Litovsky, Ruth Y. (Frontiers in Neuroscience, 2025)
IntroductionBilateral cochlear implants (BiCIs) do not restore sound localization abilities to the full extent exhibited by typical hearing (TH) listeners, partly due to poor encoding of interaural time differences (ITDs). ITD cues have been provided and investigated using synchronized research processors that ensure the precise delivery of ITD cues. These studies have been conducted in a direct stimulation setting, which bypasses the processor microphones and, in most cases, removes interaural level difference cues (ILDs). To our knowledge, this is the first study that evaluated the efficacy of synchronized stimulation in restoring sensitivity to ITDs in a free field localization experiment. This was made possible by the CCi-MOBILE, a portable and real-time processing research platform that allows for synchronizing microphone inputs.MethodsFourteen BiCI listeners were tested with experimental real-time coding strategies in comparison to unsynchronized clinical processors. We calculated the binaural cues from the acoustic stimuli at the level of microphone input.ResultsThe recordings show that the experimental coding strategies in this study deliver ITDs with greater precision than the clinical strategy. However, psychophysical testing did not show the benefit of an ITD-encoding strategy in improving localization in a free field. The ITD encoding strategies preserved ITDs, which better differentiated unique loudspeaker locations than interaural level differences (ILDs), suggesting that listeners could achieve improved performance if they accessed these cues. As expected, ILDs were similar across all strategies, including the ITD encoding strategies. The lack of improvement in localization performance is likely because ILDs remained to be the dominant cue in acute localization testing, even when ITD cues were available.DiscussionProviding BiCI listeners with adequate experiences with ITD cues may be necessary to shift their reliance from ILD dominance to a combined reliance on ILD and ITD cues in free-field conditions. The CCi-MOBILE could enable take-home practice with novel stimulation strategies for extended experiences and long-term evaluation in real-world listening environments.